Gestão sustentável de portfólios imobiliários no mercado brasileiro: os desafios para se adequar ao cenário ESG - Rodrigues Netto, João (Universidade Federal de São Carlos, 2022)
With the growing concern about climate change and the urgent need to seek sustainable development, environmentally sustainable and responsible business practices have become increasingly present in the strategic and operational activities of corporations. Sustainability is increasingly highlighted as a decisive factor for decision-making, and, in the corporate universe, a concept that has been gaining prominence is that of responsible investment, which is supported by three pillars: Environmental, Social and Governance (ESG). The Global Real State Sustainability Benchmark (GRESB) was launched in 2009 as a way of evaluating the behavior of real estate investment funds in relation to the management of their assets in the face of ESG issues, making it possible to compare the ESG performance of the asset portfolio of different funds and providing standardized and validated data for the capital market. In the present internship, we carried out the collection of data and the preparation of the necessary documentation for the submission of several reports for evaluation by the GRESB. The experience was important to enable direct experience in the area of corporate environmental management, enabling training in new topics related to sustainability, as well as a critical assessment of this topic in the Environmental Management and Analysis course.
Sustainable management of real estate portfolios in the Brazilian market: the challenges to adapt to the new ESG scenario
Keywords: ESG; Gestão Ambiental; GRESB; Real Estate; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO::GARANTIA DE CONTROLE DE QUALIDADE